An analysis of the risks of letter of credit in conventional and Islamic banks in Jordan - Alamaren, Emad Mohammad Hussien (2021)
The past few years have witnessed a widespread movement of goods between parties located in different states by utilizing letter of credit. Letter of credit has continued to play a huge role in expanding international trade since it is considered the most secure and stable banking service through which banks can finance foreign trade operations such as import and export. Although a letter of credit is considered a strong guarantee for the buyer and seller in international trade in which it gives their transactions the needed security and stability, this banking service involves some risks, which could face the Jordanian exporters and importers during its implementation in international trade. This study aims to identify the letter of credit problems facing the Jordanian exporters, importers, conventional and Islamic banks. It also analyses how the absence of the legal text regarding letter of credit in Jordan has affected the risk emergence ratio. Through a qualitative and doctrinal legal approach, this study analyses the organization of UCP 600 regarding the compliance standards and the fraud exception and its impact on Jordan. It also examines, via interviews with Jordanian bankers, academicians, and judges, the perceptions of issuing a law to regulate letter of credit transactions in Jordan. The findings reveal that the absence of the legal text regarding the letter of credit in Jordan has imposed a significant burden on the Jordanian conventional and Islamic banks since Jordanian commercial laws are not fully allocated to the letter of credit. More importantly, Jordanian exporters and importers face significant challenges in coping with the requirements imposed by the UCP 600. Therefore, this study recommends that the Jordanian legislator has to issue a regulation fully allocated to the letter of credit for further harmonization of Jordanian law with the international regulations, besides flexibility in practice, and to minimize the risk emergence ratio in the letter of credit transactions.